PENGARUH LITERASI KEUANGAN, LIFE STYLE, FINANCIAL ATTITUDE DAN SELF-CONTROL TERHADAP FINANCIAL MANAGEMENT BEHAVIOR (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS DR SOETOMO SURABAYA, 2023)
This study aims to determine the significant effect of financial literacy, life style, financial attitude, and self-control to financial management behavior. The population used is all the people of Surabaya City who have used Shopee Paylater. The sampling technique uses a non-probability sampling method with purposive sampling. the sample in this study amounted to 100 respondents. Collecting data in this study using a questionnaire. The analysis technique used is multiple linier regression analysis. The results of this study indicate that simultaneously the financial management behavior of buy now paylater users is significantly influenced by financial literacy, life style, financial attitude, and self-control. Partially, the financial management behavior of users of buy now pay later is significantly influenced by life style, financial attitude, and self-control, but not affected by financial literacy.